2019
DOI: 10.1186/s12974-019-1554-9
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of curtailing immune susceptibility in an Alzheimer’s disease model

Abstract: Background Currently, there are no effective therapeutic options for Alzheimer’s disease, the most common, multifactorial form of dementia, characterized by anomalous amyloid accumulation in the brain. Growing evidence points to neuroinflammation as a major promoter of AD. We have previously shown that the proinflammatory cytokine TNFSF10 fuels AD neuroinflammation, and that its immunoneutralization results in improved cognition in the 3xTg-AD mouse. Methods Here, we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 75 publications
5
39
0
Order By: Relevance
“…This nding is particularly interesting in light of reports that Aβ itself may have innate immune functions like antimicrobial activity [59,72] and that disruption of immune pathways attenuates Aβ burden [89]. Restoration of increased splenic Foxp3 + Tregs to basal levels has previously been shown to coincide with a reduction in the expression of Aβ in the hippocampus of 3xTg-AD males [27]. Using CY, we see similar lessening of Aβ burden in the cortex of 3xTg-AD males and females.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This nding is particularly interesting in light of reports that Aβ itself may have innate immune functions like antimicrobial activity [59,72] and that disruption of immune pathways attenuates Aβ burden [89]. Restoration of increased splenic Foxp3 + Tregs to basal levels has previously been shown to coincide with a reduction in the expression of Aβ in the hippocampus of 3xTg-AD males [27]. Using CY, we see similar lessening of Aβ burden in the cortex of 3xTg-AD males and females.…”
Section: Discussionsupporting
confidence: 63%
“…Since human Aβ has recently been reported in the spleens of 15-month-old 3xTg-AD males [27] and blood of 5-9-month-old 3xTg-AD females [23], we may speculate that peripheral Aβ might further exacerbate peripheral immune responses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are observations that the number of Treg cells becomes increased in the blood of the patients with mild cognitive impairment (MCI) and AD [180]. Moreover, Di Benedetto et al [181] demonstrated that the number of FoxP3-positive cells, a key marker of Tregs, was significantly elevated in the hippocampus of post-mortem AD samples as compared with that of age-matched controls. A similar phenomenon was observed in the brains of transgenic AD mice.…”
Section: Activation Of Immunosuppressive Network With Aging and Alzhementioning
confidence: 99%
“…Environmental factors, such as trauma and stressful life events, profoundly alter neural structure and functional plasticity of the brain, drives changes in physiology and behavior, and contributes to a variety of mental disorders [5]. Although the mechanism underlying PICS remains largely unexplored, the pathobiology of psychiatric conditions is closely linked to inflammatory processes [22][23][24]. Similarly, we showed signs of hippocampal inflammation in the form of glia overactivation and hypersecretion of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 53%